PI3K Functions in Cancer Progression, Anticancer Immunity and Immune Evasion by Tumors - Francesco Dituri; Antonio Mazzocca; Gianluigi Giannelli; Salvatore Antonaci (Clinical and Developmental Immunology)
The immunological surveillance of tumors relies on a specific recognition of cancer cells and their associate antigens by leucocytes of innate and adaptive immune responses. However, a dysregulated cytokine release can lead to, or be associated with, a failure in cell-cell recognition, thus, allowing cancer cells to evade the killing system. The phosphatidylinositol 3-kinase (PI3K) pathway regulates multiple cellular processes which underlie immune responses against pathogens or malignant cells. Conversely, there is accumulating evidence that the PI3K pathway is involved in the development of several malignant traits of cancer cells as well as their escape from immunity. Herein, we review the counteracting roles of PI3K not only in antitumor immune response but also in the mechanisms that cancer cells use to avoid leukocyte attack. In addition, we discuss, from antitumor immunological point of view, the potential benefits and disadvantages arising from use of anticancer pharmacological agents targeting the PI3K pathway.